Description of the Characteristics of Five Bedding Materials and Association With Bulk Tank Milk Quality on Five New York Dairy Herds - Alanis, Valeria M.; Zurakowski, Michael; Pawloski, Deb; Tomazi, Tiago; Nydam, Daryl V.; Ospina, Paula A. (Frontiers in Veterinary Science, 2021)
The objectives of this prospective and descriptive study were to:1) describe bedding bacterial counts, pH, and dry matter (DM) of 5 different bedding types (manure solids, sand, straw, paper fiber, and recycled sand) and 2) evaluate the association between bedding bacterial counts with bulk tank milk quality.This study took place on 5 conveniently selected commercial dairy herds, each with a predominant bedding material in lactating pens. Bedding samples (used n=237; fresh n=53) were collected monthly from July 2018 to July 2019 following a SOP to minimize sampling variability.A bulk tank (BT) milk sample (n=40) was collected on the same day unless milk had been picked up prior to arrival. Both BT and bedding samples were submitted to the laboratory for culture and bacterial identification and quantification of Streptococcus spp, Coliforms, and Non-coliforms, as well as detection of several pathogens of mastitis importance.SCC was evaluated in BT samples. Within bedding type, the correlation between bedding characteristics and bacterial counts in bedding was evaluated using Pearson correlation. Within bedding type, the correlation between bacterial counts in bedding samples and bacterial counts in BT was determined. Kruskal-Wallis test was used to evaluate the bacterial count by bedding type, and to evaluate BT SCC differences based on bedding type. In fresh bedding, bacterial counts were generally higher for manure solids for all bacterial groups compared to other materials. In used samples, organic materials had the highest levels of all bacterial groups. The proportion of samples with detectable organisms of mastitis importance varied within and among herds, both in bedding and BT samples throughout the study period. In bedding samples, a higher DM had the lowest levels of bacterial growth compared to those with lower DM. No associations between BT bacteria counts and bedding bacterial counts were observed. No association between bulk tank somatic cell counts based on bedding type was observed. Despite using an SOP for bedding sampling in an effort to consistently collect samples, we still observed a large amount of variability, both within and among bedding samples. This variability may have obscured any potential association between BT milk quality and bedding type.